KAJIAN BENTUK, FUNGSI DAN KREATIVITAS RUMAH RAJUT SYAFIR KOTO LAWEH - Hendra, Hendra; Harissman, Harissman; Nofrial, Nofrial; Ferawati, Ferawati; Zam, Riswel (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2023)
The hand-knitting craft